Pengaruh Kompensasi Dan Lingkungan Kerja Fisik Dan Kinerja Karyawan Di Universitas XYZ - Adhista, Vania; Luturlean, Bachruddin Saleh (eProceedings of Management, 2024)
In an increasingly competitive work world, companies must ensure that their employees feel valued andwork in conditions that support productivity. Fair compensation and a comfortable physical workenvironment are two important factors that are believed to improve employee performance. Therefore, thisresearch focuses on how these two variables influence performance at XYZ University. The purpose of thisresearch is to determine and analyze the influence of compensation and work environment on employeeperformance at XYZ University. The research method uses quantitative methods with a descriptivedescriptive research type. The sample for this research was 175 employees at XYZ University. The dataanalysis techniques used are descriptive analysis and multiple regression analysis. These descriptiveresults show that the three variables are in the good category, with compensation having no positive andinsignificant effect, while the work environment has a positive and significant effect on employeeperformance.Keywords-multiple regression analysis, compensation, employee performance, physical work environment,XYZ university.